TIS7 induces transcriptional cascade of methylosome components required for muscle differentiation - Lammirato, Andrea (BMC Biol, 2016)
BACKGROUND: TPA Induced Sequence 7 acts as a transcriptional co-regulator controlling the expression of genes involved in differentiation of various cell types, including skeletal myoblasts. We and others have shown that TIS7 regulates adult myogenesis through MyoD, one of the essential myogenic regulatory factors. RESULTS: Here, we present data identifying ICln as the specific, novel protein downstream of TIS7 controlling myogenesis. We show that TIS7/ICln epigenetically regulate myoD expression controlling protein methyl transferase activity. In particular, ICln regulates MyoD expression via its interaction with PRMT5 by an epigenetic modification that utilizes symmetrical di-methylation of histone H3 on arginine 8. We provide multiple evidences that TIS7 directly binds DNA, which is a functional feature necessary for its role in transcriptional regulation. CONCLUSION: We present here a molecular insight into TIS7-specific control of MyoD gene expression and thereby skeletal muscle differentiation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12915-016-0318-6) contains supplementary material, which is available to authorized users.